The Urgency of Legal Politics in the Draft Law on Religious Harmony - Setiyowati, Indah (Law Development Journal, 2021)
The constitution guarantees the rights and obligations of the Indonesian people, one of which is religious harmony, the conflicts that have occurred to the present day encourage the Government to create higher and binding regulations and have permanent legal force. The purpose of this paper is to find out about legal politics, efforts to create an orderly and harmonious relationship between religious communities and legal politics contained in the Draft Law on Religious Harmony. In this study the researcher used a normative juridical research method, which in this study the researcher took a literature study. Legal politics is a state policy (policy) through state agencies authorized to set the desired regulations. Efforts to create orderly and harmonious relations between religious communities need to pay attention to socio-cultural factors and legal factors. Then, politics in the draft Law on Religious Harmony, namely the purpose of organizing in Religious Harmony, it is necessary to have the rights and obligations of each individual in religion, then to maintain the harmony of religious life it is necessary to have rules that regulate activities that support religious harmony. The activities in question are; Commemoration of holidays, Spreading religion, Funeral of corpses, and Establishment of synagogues.